Progress : how one idea built civilization and now threatens to destroy it - McDonald, Samuel Miller (St. Martin's Press, 2025)
"Progress is power. Narratives of progress, the stories we tell about whether a society is moving in the right or the wrong direction, are immensely potent. Progress has built cities, flattened mountains, charted the globe, delved the oceans and space, created wealth, opportunity, and remarkable innovation, and ushered in a new epoch unique in our planet's 4.5-billion-year history. But [the author posits that] the modern story of progress is also a very dangerous fiction. It shapes our sense of what progress means, and justifies what we will do to achieve it--no matter the cost. We continue to subscribe to a set of myths about dominion, growth, extraction, and expansion that have fueled our success, but now threaten our--and all species'--existence on a planet in crisis. ... Geographer Samuel Miller McDonald offers a radical new perspective on the myths upon which the modern world is built, illuminating its destructive lineage and suggesting an urgent alternative"--